Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.12968/hmed.2016.77.8.454
|View full text |Cite
|
Sign up to set email alerts
|

Female gender and cardiovascular disease

Abstract: Despite a generalized belief that women are protected from cardiovascular disease, this remains the leading cause of death in women. This review focuses on differences in symptomatology, diagnostic modalities and therapeutic strategies in women with regard to cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The different pathophysiological conditions of heart disease in women and the adverse cardiac outcomes caused by serum Mg deficiency may account for the sex-related differences found in this study. Women are more vulnerable than men to CVD ( 12 , 13 ) ; women also more often have a longer QTc interval than men ( 28 , 29 ) , which is associated with an increased risk of life-threatening cardiac arrhythmias (such as torsade de pointes and polymorphic ventricular tachycardia) and sudden cardiac death ( 30 , 31 ) . Severe serum Mg deficiency has been correlated with torsade de pointes and certain ventricular tachycardia events; intravenous Mg is regarded as the treatment of choice in these cases, even if hypomagnesaemia is not present ( 32 , 33 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different pathophysiological conditions of heart disease in women and the adverse cardiac outcomes caused by serum Mg deficiency may account for the sex-related differences found in this study. Women are more vulnerable than men to CVD ( 12 , 13 ) ; women also more often have a longer QTc interval than men ( 28 , 29 ) , which is associated with an increased risk of life-threatening cardiac arrhythmias (such as torsade de pointes and polymorphic ventricular tachycardia) and sudden cardiac death ( 30 , 31 ) . Severe serum Mg deficiency has been correlated with torsade de pointes and certain ventricular tachycardia events; intravenous Mg is regarded as the treatment of choice in these cases, even if hypomagnesaemia is not present ( 32 , 33 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Although several retrospective studies have shown that low serum Mg was associated with an increased risk of hospitalisation and all-cause mortality ( 10 , 11 ) , the relationship between serum Mg and cardiovascular mortality in PD patients has not been rigorously studied. In addition, female patients in the general population are more vulnerable to CVD ( 12 , 13 ) . A prospective cohort study reported that higher plasma Mg concentrations and dietary Mg intake were associated with a lower risk of sudden cardiac death in women ( 14 ) .…”
mentioning
confidence: 99%